2021
DOI: 10.3389/fonc.2021.728018
|View full text |Cite
|
Sign up to set email alerts
|

From Immunogenic Cell Death to Immunogenic Modulation: Select Chemotherapy Regimens Induce a Spectrum of Immune-Enhancing Activities in the Tumor Microenvironment

Abstract: Cancer treatment has rapidly entered the age of immunotherapy, and it is becoming clear that the effective therapy of established tumors necessitates rational multi-combination immunotherapy strategies. But even in the advent of immunotherapy, the clinical role of standard-of-care chemotherapy regimens still remains significant and may be complementary to emerging immunotherapeutic approaches. Depending on dose, schedule, and agent, chemotherapy can induce immunogenic cell death, resulting in the release of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 129 publications
2
78
0
Order By: Relevance
“…Noteworthily, the immune microenvironment of CRC tumors can be modulated by cancer treatments. For example, cancer chemotherapy has been shown to induce cell necrosis that releases immunostimulatory danger signals into the TME [ 24 ] and to increase tumor infiltration by cytotoxic CD4 + T cells [ 25 ]. Whether such chemotherapy-induced tumor inflammation could enhance responsiveness to subsequent ICI in mCRC is currently under investigation (e.g., METIMMOX clinical trial: NCT03388190).…”
Section: Overview Of Colorectal Tumor Subtypes and Associated Immune ...mentioning
confidence: 99%
“…Noteworthily, the immune microenvironment of CRC tumors can be modulated by cancer treatments. For example, cancer chemotherapy has been shown to induce cell necrosis that releases immunostimulatory danger signals into the TME [ 24 ] and to increase tumor infiltration by cytotoxic CD4 + T cells [ 25 ]. Whether such chemotherapy-induced tumor inflammation could enhance responsiveness to subsequent ICI in mCRC is currently under investigation (e.g., METIMMOX clinical trial: NCT03388190).…”
Section: Overview Of Colorectal Tumor Subtypes and Associated Immune ...mentioning
confidence: 99%
“…However, even though ICD has clear connection with the UPR and triggers the release of immunomodulatory molecules, it is presently unknown if it can also be a source of factors that transmit UPR and pro-inflammation transcellularly. This is relevant since numerous clinical trials are currently testing the ICD paradigm ( 166 ). Based on the arguments presented in this review article, cell-nonautonomous UPR as a result of ICD could paradoxically ignite dysregulation of local immunity.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The full publication is anxiously awaited as this large study may further help elucidate mechanisms of response and resistance. Additionally, Zhang et al [76] showed in a phase 0 trial that systemic use of interferon-gamma could increase MHC-I expression and T-cell infiltration in patients with synovial sarcoma and myxoid round cell liposarcomas, leading to a phase II trial of interferon-gamma with pembrolizumab (NCT03063632). While no results are yet published for this study, this is another unique strategy to target early immune responses and restore immunogenicity in cold sarcomas.…”
Section: Overcoming Resistance: Future Directionsmentioning
confidence: 99%
“…One of the most potential inducers of tumor immunogenicity is traditional chemotherapy, with various agents inducing immunogenic cell stress, production of innate immunity attractants including type 1 interferons, and inflammasome induction [ 77 ] . In particular, doxorubicin has been shown in a variety of preclinical tumor models to potently induce the production of DAMPs and type 1 interferons promoting downstream transcription of interferon-stimulated genes, and ultimately increased DC and T cell infiltration in tumor deposits [ 78 - 83 ] .…”
Section: Emerging Mechanisms Of Resistancementioning
confidence: 99%